Konsep Fungsi Semikontinu - Malahayati Malahayati (Program Studi Matematika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2014)
This paper discusses the basic concepts and some of semicontinuous function, begins by introducing the concept of upper limit and lower limit.